PATU2 Novel truncation mutation of PRNP causes chronic diarrhoea, sensory neuropathy and autonomic failure associated with prion protein deposition in the cerebral blood vessels and small bowel. Issue 11 (22nd October 2010) - Mead, S; Linehan, J; Beck, J; Caine, D; Gandhi, S; Wadsworth, J D F; Joiner, S; Gallujipali, D; Hyare, H; Lees, A; Holton, J; Sandberg, M; et al.
Abstract : The inherited prion diseases (IPD) are a group of dominantly inherited neurodegenerative disorders caused by mutation of the prion protein gene ( PRNP ). Although clinically heterogeneous, IPDs are generally associated with progressive dementia, ataxia and with characteristic pathology. Here we describe a quite distinct and consistent phenotype in nine patients from a family with a novel Y163X PRNP truncation mutation. The major clinical features consist of chronic diarrhoea, profound autonomic failure and a predominantly axonal sensory peripheral neuropathy in early adulthood. Prior to genetic analyses, the clinical diagnosis was hereditary sensory and autonomic neuropathy (HSAN), which was followed by cognitive decline and seizures only much later, in the fifth to sixth decade. Neuropathological assessments reveal extensive central nervous system prion protein deposition including cerebral amyloid angiopathy and secondary tauopathy. Remarkably, abnormal prion protein deposition was also seen in the duodenum which may have contributed to presentation with diarrhoea. Molecular analysis of proteinase-resistant material from brain shows evidence of aggregation and covalent cross-linking of a misfolded and truncated prion protein entity. The association of autonomic failure, diarrhoea, and neuropathy should prompt PRNP testing and precautions for iatrogenic transmission. Abnormal anchorless PrP may deposit in peripheral tissues and be associated with nonneurological presentations.